Survey of Provider Preferences Regarding the Route of Misoprostol for Induction of Labor at Term - Towns, Rachel; Quinney, Sara K.; Pierson, Rebecca C.; Haas, David M. (American Journal of Perinatology Reports, 2017)
Objective To survey obstetrical provider preferences regarding use of misoprostol for induction of labor (IOL).Methods An anonymous 25-question survey was distributed at an American College of Obstetricians and Gynecologists (ACOG) joint District V and VII Meeting in 2014 to obstetrics providers. The same survey was sent electronically to local providers. A separate survey was emailed to the labor and delivery nurses at two of the teaching hospitals in Indianapolis. The surveys queried provider demographics, dosing practice for misoprostol, opinions regarding different dosing strategies, and instructions on buccal administration.Results A total of 113 (46.5%) providers responded. Of these, 92.9% used misoprostol for IOL, 73% preferred the vaginal route, 20% preferred buccal administration, and 7% oral administration. Only resident physician and midwife providers endorsed buccal route preference. Being a midwife independently predicted a preference for using buccal misoprostol (odds ratio [OR]: 125.8, 95% confidence interval [CI]: 7.9–1992.3). Additionally, 44 nurses completed the survey regarding administration techniques of buccal misoprostol. Also, 54.5% of nurses correctly instructed their patients on buccal administration techniques.Conclusion Although not extensively studied, one-fifth of providers, particularly nurse midwives, prefer buccal administration of misoprostol for IOL. The majority of nurses correctly administered buccal misoprostol. There may be a need for further study and education about buccal administration of misoprostol for IOL.
Keywords: misoprostol; labor induction; provider preference; buccal; vaginal